From Prague to Jerusalem : An Uncommon Journey of a Journalist - Kubic, Milan J. (Book collections on Project MUSE., 2017)
After spending his childhood in Nazi-occupied Czechoslovakia and witnessing the Communist takeover of his country in 1948, a young journalist named Milan Kubic embarked on a career as a Newsweek correspondent that spanned thirty-one years and three continents, reporting on some of the most memorable events in the Middle East. Now, Kubic tells this fascinating story in depth. Kubic describes his escape to the US Zone in West Germany, his life in the Displaced Persons camps, and his arrival in 1950s America, where he worked as a butler and factory worker and served in a US Army intelligence unit during Senator Joe McCarthy's witch-hunting years. Hired by Newsweek after graduating from journalism school, Kubic covered the White House during the last year of Dwight D. Eisenhower's presidency, the US Senate run by Lyndon Johnson, and the campaign that elected President John F. Kennedy. Kubic spent twenty-six years reporting from abroad, including South America, the Indian subcontinent, and Eastern and Western Europe. Of particular interest is his account of the seventeen years--starting with the Six Day War in 1967--when he watched the Israeli-Palestinian conflict from Beirut and Jerusalem. In From Prague to Jerusalem, readers will meet the principal Israeli participants in the Irangate affair, accompany Kubic on his South American tour with Bobby Kennedy, take part in his jungle encounter with the king of Belgium, witness the inglorious end of Timothy Leary's flight to the Middle East, and observe the debunking of Hitler's bogus diaries. This riveting memoir will appeal to general readers and scholars interested in journalism, the Middle East, and US history and politics.